ANALYZING THE ESSENCE BETWEEN CEREMONIAL SPACE WITH ISLAMIC CENTER MOSQUE EXPRESSION IN WEST TULANG BAWANG - Jessica Virginia Amaris (Riset Arsitektur (RISA), 2019)
Abstract- A mosque is a religious place for followers of Islam all over the world, as well in Indonesia, which is the country with the largest number of Muslims society in the world. Thus will affect the high needs of Muslims society for the mosque architecture building that used to perform rituals of worship activity. In this modern era, the shape and style of mosque architecture gets more diverse because of the influence of construction technology. In addition, the diversity is also due to the absence of concrete provisions that discuss the form and style of architecture in the Alquran. The diversity in the form and style of mosque architecture will result in different architectural expression for mosque building. Due to these phenomena, many people are questioning the proper mosque’s form.Masjid Islamic Centre Tulang Bawang Barat (Tubaba) is one of the mosques that meets the object research’s criteria because it doesn’t have universal mosque’s form that generally uses dome. Mosque as a sacred building requires a clear symbolization of the physical elements of the mosque building. This symbolization can be described in the form of activities, such as pray. Undertaken activities will result in spatial space analysis of the mosque which can then be reviewed by the theory of form and meaning. The research was done by applying the theory of anatomy and scope of the building. Furthermore, a review based on the theory of form and meaning is done to see if Masjid Tubaba’s building meets the criteria of symbolization of activities that will result in spatial space of the mosque. As a result, this research will obtained a new standard on the spatial space of the mosque resulting from the symbolization of ritual activities. Key Words: mosque, expression, spatial space, symbolization, ritual activity